Concurrent Carotid Endarterectomy and off-Pump Coronary Artery Bypass Graft Surgery in Bangladesh: a Prospective Cohort Study - Ranjan, Redoy; Adhikary, Dipannita; Saha, Heemel; Saha, Sanjoy Kumar; Mandal, Sabita; Hasan, Kamrul; Adhikary, Asit Baran (Anwer Khan Modern Medical College Journal, 2018)
Background: A patient of ischemic coronary artery disease (IHD) with additional carotid artery stenosis (CAS) has been distinguished as a high risk group for both heart and cerebral inconveniences following surgical intervention. We review the outcome of concurrent carotid endarterectomy (CEA) and off-pump coronary bypass grafting (OPCABG)in a patient undergoing surgical revascularization for IHD and CAS in a single surgeons practice. Materials and Methods: In the vicinity of January 2012 and December2016,fifteen patients experienced OPCABG and CEA associatively in a single Surgeon's Practice. Majority 46.66% patient have 75-90% Carotid artery stenosis and 40%patients experienced right sided lesion, though 53.33% experienced left sided lesion. 33.33% patients were found Left main coronary artery disease (>50% lesion) and 100% patients have had significant LAD lesion in this study. CEA was performed before OPCABG in all cases. Result: Themean age was 62.5±2.8 years; 80% were male. 13.33% had a perioperative stroke while one of them had TIAs (6.6%). Mean ICU stay was 36.6±4.5 hours and patients were released in 10±2 days. There was no mortality in the early postoperative period and co-morbidity was less significant; only 6.6% myocardial ischemia, 13.33% Atrial fibrillation, 6.66% TIA, and 13.33% Stroke. Conclusion: A combined strategy by means of CEA with OPCABG is safe and savvy in view of the satisfactory consequences of morbidity and mortality rates and also short ICU and hospital stay status. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 15-21